2010
DOI: 10.1002/jcu.20676
|View full text |Cite
|
Sign up to set email alerts
|

Measurement issues in the sonographic assessment of tennis elbow

Abstract: Sonography is increasingly being used for assessment in tennis elbow research and clinical practice, but there are a lack of data regarding its validity, reliability, and responsiveness to change for this application. Studies using the modality were reviewed to establish current levels of evidence for these measurement properties. There is reasonable evidence regarding its validity for identifying tennis elbow tendinopathy, but a lack of data addressing its reliability and responsiveness. Practical issues affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…26,32,35 In many studies investigating LE with the use of US, the presence of spurs is described as a sonographic characteristic of tendinopathy. 8,22,29,30 Bony spurs might occur with a higher prevalence or size in patients with LE. However, based on the findings in our study, the clinical value of describing a bony spur is limited because it is a very common phenomenon.…”
Section: Bony Spursmentioning
confidence: 99%
See 1 more Smart Citation
“…26,32,35 In many studies investigating LE with the use of US, the presence of spurs is described as a sonographic characteristic of tendinopathy. 8,22,29,30 Bony spurs might occur with a higher prevalence or size in patients with LE. However, based on the findings in our study, the clinical value of describing a bony spur is limited because it is a very common phenomenon.…”
Section: Bony Spursmentioning
confidence: 99%
“…1,17,24,40 Several studies have adopted some of these US features in the assessment of patients with LE. 4,5,22,23,25,29 However, the described tendinopathic changes have not been compared with those present in the general population, and the standards lack a scientifically based consensus. The establishment of valid standards will help to avoid misinterpretation and distinguish between pathological and benign US findings.…”
mentioning
confidence: 99%
“…1,27,33,61 Several studies have described these US features in patients with LE. 7,30,32,36,48 Our objective was to determine whether 1 injection of PRP or glucocorticoid reduces pain more effectively than isotonic saline in adults with LE.…”
Section: -In-5mentioning
confidence: 99%
“…Blood vessels are seldom visible inside a healthy endotendon. Although neovascularization in ultrasound imaging is not always revealed in every tendinopathic tendon, it is still regarded as a hallmark of tendinopathy 19 . We found that all ultrasound features had higher scores in the Collagenase group than in the Control group, except for calcification at weeks 1 and 4 .…”
Section: Discussionmentioning
confidence: 99%